2019
DOI: 10.3889/oamjms.2019.361
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Characteristics and Variants of Prostatic Artery in Patients of Benign Hyperplasia Prostate by Digital Subtraction Angiography

Abstract: AIM: This work is aimed to describe anatomical features and variants of the prostatic artery (PA) using digital subtraction angiography (DSA). METHODS: This is a descriptive statistic study. We reviewed the DSA of 348 patients, who had a PA embolisation to reduce the benign prostatic hyperplasia (BPH) symptoms at Radiology Department of Bach Mai Hospital from Oct – 2014 to Oct – 2018. RESULTS: PA was found at 660 pelvic halves, of which 30 pelvic halves (4.5%) had two PAs, 630 pelvic halves had one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…This discovery is consistent with findings of Nguyen et al [ 30 ], Bilhim et al[ 31 ] Wang et al [ 13 ], de Assis et al[ 9 ] and Amouyal et al[ 19 ] This study is CTA based compared to DSA (+/- CBCT) in most other studies. This study was made to match daily practices (CBCT not available in Ghana) and to stand as a pre procedural planning [ 32 ], knowing especially that the benefit of CBCT is precisely to detect potential accessory PA. For instance, Nguyen et al [ 30 ] found single prostate artery in 630 pelvic halves out of 660 in a Vietnam population (. Bilhim et al[ 16 ] reported single PA in 57% of 150 male pelvic halves among adult in Portugal .…”
Section: Discussionsupporting
confidence: 92%
“…This discovery is consistent with findings of Nguyen et al [ 30 ], Bilhim et al[ 31 ] Wang et al [ 13 ], de Assis et al[ 9 ] and Amouyal et al[ 19 ] This study is CTA based compared to DSA (+/- CBCT) in most other studies. This study was made to match daily practices (CBCT not available in Ghana) and to stand as a pre procedural planning [ 32 ], knowing especially that the benefit of CBCT is precisely to detect potential accessory PA. For instance, Nguyen et al [ 30 ] found single prostate artery in 630 pelvic halves out of 660 in a Vietnam population (. Bilhim et al[ 16 ] reported single PA in 57% of 150 male pelvic halves among adult in Portugal .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding types II and III, they are less common than types I and IV, both in the present and in the largest part of previous work, although their prevalence varies significantly among the reports (6-31.1% and 4.7-23.8%, respectively). Interestingly, the herein-reported prevalence of type V (9%) is significantly higher compared to all but one [ 6 ] of the previous studies. The same applies to the main representative of type V in this work, namely, PA origin from the accessory IPA.…”
Section: Discussioncontrasting
confidence: 69%
“…In the first part of this study, the type of PA origin was systematically investigated with CTA and DSA for the first time in a Greek population with BPH. Several studies from other countries have utilized the same system for the categorization of PA origin, and, not surprisingly, there is variance between the results of the present and previous studies [ 3 - 6 , 8 - 11 ], likely due to racial and ethnic differences in pelvic arterial anatomy. In the studied population, the prevalence of the two most common types (I and IV, 31% each) was lower and higher, respectively, compared to the majority of previous articles.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There are cases when we can identify IPA and IPA accessories, which must not be confused with the PA. At the level of accessory IPAs, we can find the origin of the middle rectal artery, which has a characteristic pattern of enhancement that cannot be mistaken with the prostatic blush [12] (Figure 2);…”
mentioning
confidence: 99%